Monitoring and Assessment for the Susceptibility of Landslide Changes After the 2017 Ms 7.0 Jiuzhaigou Earthquake Using the Remote Sensing Technology - Guo, Xinyi; Fu, Bihong; Du, Jie; Shi, Pilong; Li, Jingxia; Li, Zhao; Du, Jiaxin; Chen, Qingyu; Fu, Han (Frontiers in Earth Science, 2021)
Monitoring the change of post-seismic landslides could provide valuable information for geological disaster treatment. The Jiuzhaigou Ms7.0 earthquake has triggered a large number of landslides in the Jiuzhaigou UNESCO natural heritage site, which provides a unique opportunity for monitoring the spatio-temporal characteristics and exploring the impact factors of post-seismic landslides change. In this study, the spatio-temporal characteristics of landslides and their post-seismic changes are analyzed using multi-source, multi-temporal, and multi-scale remote sensing data combining with field study. SVM classification, visual interpretation, field investigation, and GIS are employed to extract landslides and analyze their spatial distribution patterns. Moreover, the CF method is used to explore the sensitivity of landslides and to find key impact factors. Our results show that the net increase area of landslide is 1.2 km2 until September 27, 2019, which are induced by the expansion of coseismic landslide, post-seismic landslide, and the expansion of vegetation degradation. The highest net increase rate of post-seismic landslide change does not distribute on the regions with the highest density of coseismic landslides. The sensitivity of post-seismic landslide change is greatly influenced by slope, altitude, aspect, PGA, fault, and strata. It is higher in the area with low sensitivity of coseismic landslide. This study also suggests that the potential landslides will most likely occur in the unstable slope region affected by the additional driving force. Therefore, great attention should be paid to identify and prevent the potential landslides on unstable slopes in addition to treatments of the sliding slopes. This study provides a good example for post-seismic landslide treatment in mountainous regions with a steep slope and deep valley.